The System of Gelled Foam of Clay-in-water Suspension for the Preparation of Lightweight Insulating Refractory: Part I. Formation and Gelling of Clay-Based Foam - Iman Nazeni (Institute for Research and Community Services (LPPM) ITB, 1961)
Under neutral conditions colloidal plates of clay in water are negatively charged. When the pH of the clay-in-water dispersion is lowered slightly, positive charges can develop on the edges of the clay plates giving rise to an edge-to-face type gelation. Sodium fluosilicate, which has a rather high acidity and which is very slightly soluble in water, can be used as gelling agent. By beating a clay slip containing, a surfaceactive agent